KINERJA DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU KAMPAR DALAM MENINGKATKAN PELAYANAN IZIN REKLAME DI KABUPATEN KAMPAR - Herza Widya Putri; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The performance of Penanaman Modal Pelayanan Terpadu Satu Pintu Kampar in improving the advertisement permit service in Kampar district, it is an effort to ensure that all billboards in the Kampar district have a permit. The purpose of this research is to describe the performance used by the Penanaman Modal Pelayanan Terpadu Satu Pintu To improve the advertising clearance in Kampar and to describe the factors affecting the service performance Penanaman Modal Pelayanan Terpadu Satu Pintu To improve billboards permits in Kampar. Focus study in this study is performance service Penanaman Modal Pelayanan Terpadu Satu Pintu To improve billboards permits in Kampar. Informant in this research is the management of Perzinan services, licensing services Staff, business owner that take care of the permission of billboards, business that do not take care of permits. The methods used in this study included in qualitative and data collection techniques are interviews and observations. Based on the results of known research service Penanaman Modal Pelayanan Terpadu Satu Pintu In improving the service of billboards permit is not optimal. Due to the lengthy process of advertising permit management, the duration of the licensing process is not due to the constraints of facilities and its main process but due to pending approval from the main manager of the advertising licensing service Penanaman Modal Pelayanan Terpadu Satu Pintu. Licensing constraints by the community actually does not lie in its main procedure but from the authorities in the management and approval of the licensing to be published. There are several factors that affect the service performance Penanaman Modal Pelayanan Terpadu Satu Pintu It is work satisfaction, efficiency, effectiveness and the awareness of the billboard owner. Keywords: performance, service, billboards